98th AES Convention - 25-28.02.1995 - PARIS - Polish AES Section Report - SANKIEWICZ, M. (Archives of Acoustics, 1995)
Audio Engineering Society Conventions became traditional world meetings of all scientist, engineers, industry managers, producers, dealers and even fanciers interested in the domain of sound and vision systems, equipments, facilities, components, hard - and software computer elements etc. Such meetings take place twice a year: Spring Convention in Europe (denoted with consecutive even numbers), and Fall Convention in the USA (denoted with odd ones).